Understanding politics : ideas, institutions, and issues - Magstadt, Thomas M. (Boston, Massachusetts Cengage Learning, 2021)
"Politics is a gateway to a broader and better understanding of human nature, society and the world" is the inspiration behind Magstadt's UNDERSTANDING POLITICS: IDEAS, INSTITUTIONS, AND ISSUES. The 13th Edition challenges you with its analysis of three fundamental premises: Politics is a pervasive force in modern society; government is too important to be left in the hands of a few; and the right to participate in public life is a precious thing unique to republics. Timely and relevant, it provides in-depth coverage of contemporary political issues and places them in the context of more enduring underlying questions. It focuses on key topics like ideology, citizenship, voting behavior, leadership and foreign policy as well as emerging issues, including the Trump presidency, social media in politics, Brexit, China as partner and rival, and populism and nativism as a reaction to globalism." -- Amazon.
Introduction: the study of politics -- The idea of the public good: ideologies and isms -- Utopias: model states -- Constitutional democracy: models of representation -- The authoritarian model: myth and reality -- The totalitarian model: a false utopia -- Parliamentary democracy: pros and cons of perishable governments -- Democracy or dictatorship?: transitional systems yesterday and today -- Problems of development: progress and poverty in a global age -- Political socialization: the making of a citizen -- Political participation: the limits of democracy -- Political leadership: the many faces of power -- Issues in public policy: politics, principles, priorities, and practices -- Revolution: in the name of justice -- War: politics by other means -- Terrorism: war or crimes or war crimes? -- World politics: the struggle for power -- International law and organization(s): the quest for world order.
Keywords: Political science -- Textbooks